2012
DOI: 10.5455/ijmsph.2012.1.87-92
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic profile and health care seeking behaviour of rural geriatric population of Allahabad district of UP: A cross sectional study

Abstract: Background: World population ageing is enduring, the proportion of older persons has been rising steadily, from 7 per cent in 1950 to 11 per cent in 2007, with an expected rise to reach 22 percent in 2050. Globally the population of older persons is growing at a rate of 2.6 per cent per year, considerably faster than the population as a whole which is increasing at 1.1 percent annually. The issue of health care-seeking (or medical-care) behaviour is crucial to all society. Objective: To know the Socio-demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 2 publications
4
16
1
Order By: Relevance
“…Hospitals of Bangladesh is cheap. It differs from the findings of Narapureddy et al 20 In a study conducted in rural UP, the authors found that 45.7% of the elderly persons sought treatment from private practitioner and private hospital, 32.3% from quack. Only 18.9% sought treatment from Govt.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…Hospitals of Bangladesh is cheap. It differs from the findings of Narapureddy et al 20 In a study conducted in rural UP, the authors found that 45.7% of the elderly persons sought treatment from private practitioner and private hospital, 32.3% from quack. Only 18.9% sought treatment from Govt.…”
contrasting
confidence: 55%
“…hospitals. 20 This discrepancy is may be due to lack of accessibility of Govt. health services in that reason.…”
mentioning
confidence: 99%
“…Anil Jacob Purty et al 9 in their study in a rural area of Tamil Nadu found that 78.7% of elderly were illiterate. Bayapareddy N et al 10 in a study conducted in a rural area of Allahabad District, UP found that 70.1% of the elderly were illiterate. SH Parry et al 11 in their study conducted in Kashmir found that 67.8% of the elderly in rural area were illiterate.…”
Section: Discussionmentioning
confidence: 99%
“…Similar finding was confirmed by other observers in their studies. [5][6][7][8][9][10][11][12][13][14][15] In the present study, sex distribution shows that females (57.5%) outnumbered the males (43.5%). The other researchers confirmed the similar finding whereas Shankar R et al, Narapureddy B et al, Kumar R et al and Lahiri S et al found in their studies that number of males were more than that of females.…”
Section: Discussionmentioning
confidence: 95%
“…The other researchers confirmed the similar finding whereas Shankar R et al, Narapureddy B et al, Kumar R et al and Lahiri S et al found in their studies that number of males were more than that of females. [5][6][7][8][9][10][11][12][13][14][16][17][18] The marital status of the elderly shows that 59.77% were married and 40.23% were widowed. This finding was comparable to that of a report published by United Nation Population Fund (UNFPA), where about 60% of the elderly were currently married and 38% widowed.…”
Section: Discussionmentioning
confidence: 99%